2020
DOI: 10.1101/2020.05.12.088880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating BMP9 protects the pulmonary endothelium during inflammation-induced lung injury in mice

Abstract: RationalePulmonary endothelial permeability contributes to the high-permeability pulmonary edema that characterizes acute respiratory distress syndrome (ARDS), which carries a high mortality. Circulating bone morphogeneic protein 9 (BMP9) is emerging as an important regulator of pulmonary vascular homeostasis.ObjectiveTo determine whether endogenous BMP9 plays a role in preserving pulmonary endothelial integrity, and whether loss of endogenous BMP9 occurs during lipopolysacharride (LPS)-induced lung inflammati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The Interleukin-12 family was discovered in 2007, and Interleukin-35 is a new member of it (7). Recent studies have investigated the connection between impaired immune regulation and pulmonary endothelium, which is required for pulmonary vascular local homeostasis (26). Under physiological conditions, IL-35 expression was absent or present only at very low levels in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…The Interleukin-12 family was discovered in 2007, and Interleukin-35 is a new member of it (7). Recent studies have investigated the connection between impaired immune regulation and pulmonary endothelium, which is required for pulmonary vascular local homeostasis (26). Under physiological conditions, IL-35 expression was absent or present only at very low levels in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…These results in summary showed that BMP2/4/6 induce EC permeability, likely resulting in reduced cell–cell tension. In contrast, BMP9/ALK1 signaling prevents vascular permeability and was recently shown to prevent the leakiness of the inflamed lung microvasculature [ 193 ]. BMP9-ALK1 signaling facilitates cell–cell contacts and balances the interdependency between apico-basal and lateral forces [ 194 ]; Figure 4 b,c.…”
Section: Bmp/tgfβ Signaling and Integration Of Basolateral Forcesmentioning
confidence: 99%
“…In this issue of Journal , Li and colleagues (pp. 1419–1430 ) show the power of this approach, adapting findings originally produced for pulmonary hypertension to acute respiratory distress syndrome (ARDS), a much more common problem than PAH, with an estimated 190,000 cases per year in the United States ( 9 , 10 ). They show in mice that blocking BMP9 leads to pulmonary vascular leak comparable to adding LPS, that BMP9 regulates genes involved in endothelial cell integrity, and that giving BMP9 to mice prevents vascular injury with inhaled LPS in mice.…”
mentioning
confidence: 96%